2015
DOI: 10.1111/hpb.12378
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of patient and clinician attitudes regarding surveillance after a resection of pancreatic and periampullary cancer

Abstract: Patients have an intense need for reassurance and obtain this through follow-up appointments with their oncologists. Consequently, they express few difficulties with the process. Clinicians recognize this desire for reassurance. Patients' understanding and expectations contrast starkly with clinicians' perspectives regarding prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
(93 reference statements)
3
24
0
Order By: Relevance
“…Probable relapse should not deter nor delay provision of survivorship care, but instead, offer an opportunity to improve survivorship support. Many pancreatic cancer patients convey a limited understanding of their prognosis while clinicians believe patients are aware of their recurrence risk (4). SCPs, if appropriately articulated, could stand to improve communication between physicians and patients regarding prognosis while still providing hope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probable relapse should not deter nor delay provision of survivorship care, but instead, offer an opportunity to improve survivorship support. Many pancreatic cancer patients convey a limited understanding of their prognosis while clinicians believe patients are aware of their recurrence risk (4). SCPs, if appropriately articulated, could stand to improve communication between physicians and patients regarding prognosis while still providing hope.…”
Section: Discussionmentioning
confidence: 99%
“…Little dialogue or investigation has been committed to this topic in pancreatic cancer, perhaps to the detriment of the patient. A lack of supporting evidence devoted to surveillance practices in pancreatic cancer has led to heterogeneity in follow-up and disagreement on its necessity and efficacy (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cancer survivors, patient organizations representing a range of organ-specific cancers, as well as the Danish Health and Medicines Authority have advocated that follow-up should include a broader rehabilitative focus on patients' individual needs, concerns and life-situation [1]. One reason for this is that although patients gain temporary reassurance through regular follow-up, follow-up focusing mainly on disease relapse may paradoxically increase fear and anxiety and impact negatively on uptake of everyday life [5]. Patients with pancreatic, duodenal or bile duct cancers may for example suffer from treatment-related sequelae such as fatigue, nausea, pain, exocrine and endocrine dysfunction and cognitive problems [6][7][8], all symptoms potentially influencing rehabilitation and quality of life (QOL) if not adequately addressed by health care professionals (HCPs) [9].…”
Section: Original Articlementioning
confidence: 99%
“…Qualitative investigation of the patient perspective may provide valuable insight into how patients experience follow-up, their expectations and how they perceive HCPs address their needs [10]. To our knowledge, only one study has investigated patients' and HCPs' attitudes toward surveillance after curatively intended surgical resection of pancreatic cancer [5]. This study found that patients felt reassured by frequent follow-up visits, they wanted to be informed about recurrence, and attending follow-up was 'like a walk in the park', notably as long as everything was fine [5].…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation